Multiparticulate systems of pectin-chitosan: Study of swelling and drug release - Lucinda-Silva, Ruth Meri [UNESP]; Monteiro, Karen Cristina Moutinho [UNESP]; Carvalho, Lívia de Queiróz [UNESP]; Evangelista, Raul Cesar [UNESP] (My University, 2006)
The aim of this study was to prepare multiparticulate systems of pectin:chitosan (PC:CS) and to evaluate their swelling ratio and the drug release in different environments. PC:CS particles containing triamcinolone were prepared by a complex coacervation/ionotropic gelation method in aqueous environment. The polymer ratio, the calcium concentration and the contact time of the capsules with chitosan dispersion for particles formation and the structures obtained were analyzed. The systems were characterized in relation to morphology, size, swelling, and drug release behavior. The methodology used allowed the production of spherical particles with narrow range of size distribution. The entrapment efficiency for triamcinolone was 84.31 ± 439. It was observed that the particles present a relatively low swelling ratio in acidic medium and a larger swelling ratio in enteric medium. The release profile was dependent on pH and can be related with the swelling ratio.
Keywords: Chitosan; Multiparticulate systems; Pectin; Swelling; Triamcinolone; calcium; chitosan; pectin; triamcinolone; coacervation; dispersion; drug capsule; drug release; drug synthesis; gelation; particle size; pH measurement